Resilience in Small Family Businesses during Systemic Shocks: A Literature Review on the Mediating Role of Adaptive Capacity - Novrizal; Mia Christy Patricia (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores how adaptive capacity mediates resilience in small family businesses (SFBs) during systemic shocks. Drawing from recent empirical studies, the review identifies adaptive capacity as a dynamic capability that enables SFBs to respond effectively to crises through flexible leadership, innovation, generational collaboration, and social capital. Unlike non-family firms, SFBs exhibit unique strengths and constraints rooted in socioemotional wealth, long-term orientation, and intergenerational ties. The findings highlight that adaptive capacity functions as a crucial intermediary between environmental disruption and business continuity. Contextual factors such as industry, firm size, and institutional support further influence resilience outcomes. This study contributes to the theoretical understanding of resilience by positioning adaptive capacity as a central mechanism in navigating systemic shocks.